Case Report: Treatment of the rare B-cell lymphoblastic lymphoma with scalp lesion using rotation flap - Kim, Timothy; Jung, Geena; Buckner-Wolfson, Emery; Fatemi, Ryan; Liriano, Genesis; Tal, Adit; Wang, Yanhua; Tepper, Oren; Kobets, Andrew (Frontiers in Oncology, 2023)
Introduction Leukemia is the most frequently occurring cancer in children, and lymphoblastic lymphoma (LBL) is a rare subtype. LBL are lymphoid neoplasms of B or T cell origin and are primarily treated with chemotherapy. Although cure rates among children are excellent, these patients must be monitored for relapse. Cutaneous lesions involving B-cell LBL (B-LBL) are extremely rare and here we present a patient with a worsening B-LBL scalp mass who required radical surgical excision. Case report A 6-year-old female patient with a history of a nontender scalp mass discovered at approximately 2-3 years of age was evaluated for resection of the nodule due to its size and treatment history. The patient was originally diagnosed with follicular lymphoma by punch biopsy; excision was successfully performed on this 4 cm lesion and upon examination of the skin biopsy did we get a diagnosis of B-LBL. Reconstruction of the scalp was done through the rotation flap method. The patient’s scalp healed well, and adjuvant chemotherapy was continued. There has been no reoccurrence. Discussion Here we report the rarity of B-LBL cases involving extranodal involvement in the scalp. The most common reconstruction of scalp lesions has been using free flap from the anterolateral thigh (ALT) and latissimus dorsi (LD). Our case used the rotation flap, which has its functional and cosmetic benefits. The importance of monitoring this patient is emphasized due to the dangerous consequences of B-LBL relapse. Ultimately, our successful treatment and care of this rare case can be used as guidance for similar patients in the future.